Cholelithiasis Diagnosis and Management in Thalassemia - Damayanti, Ervina Luki; Gayatri, Pramita (The Indonesian Society of Pediatric Gastroenterology, Hepatology, and Nutrition, 2024)
Background: Cholelithiasis, while infrequently found in children, carries a significant risk for those with underlying conditions like thalassemia compared to the general population. This study aimed to described the manifestations of cholelithiasis in thalassemic children. Case: A 12-year-old girl with beta-thalassemia major presented with recurrent right upper quadrant abdominal pain and vomiting. Imaging revealed cholelithiasis and choledocholithiasis. Due to complications related to her thalassemia, she underwent endoscopic retrograde cholangiopancreatography (ERCP) for gallstone removal followed by laparoscopic cholecystectomy. Post-operative management addressed post-ERCP pancreatitis and bleeding concerns. The patient recovered well and is scheduled for follow-up. Discussion: Increased bilirubin production, iron overload, and altered bile properties in beta-thalassemia contribute to cholelithiasis risk. The patient presented with typical symptoms and underwent successful laparoscopic cholecystectomy after initial management with ERCP, which led to post-ERCP pancreatitis. Conclusion: This case underscores the elevated risk of cholelithiasis in thalassemic children and the importance of early diagnosis and intervention for optimal outcomes.